Premarital Sexual Behaviour and its Impact on Health among Adolescents - Shrestha, Ram Bahadur (Journal of Health Promotion, 2019)
More than two-thirds of young people in developed nations have sexual intercourse while still in their teens. The most vulnerable group of premarital sexual behaviour are youths and adolescents. The aim of the study is to assess factors affecting premarital sex behaviours among adolescents and its impact on health. This study is based on the review of secondary information published by the relevant organization and authors in Nepal and beyond. Study materials were primarily identified searching through Electronic databases and Software bases. Age group of 10-19 called as adolescents during the period, there is drastic development in physical, cognitive, social and emotional development. There are multidimensional factors that leads to premarital sexual behaviour. Parent relationship withtheir children and family environment, societal environment, cultural and traditional rules and values, economic condition, school environment, peer's relationship, love and affairs, communications (mobiles, internet-pone movies etc.) and rules and regulation are the risk factors that affect in premarital sexual behaviour of the adolescents. Sex after marriage is fruitful but having a premarital sex with mutual understanding with full protection is not a big issue. Unwanted pregnancy, teenage pregnancy, abortion, STIs, HIV/AIDS, regrets, guilt, loss of self-respect, depression, loss of family support, substance abuse and even suicidal death  are the health impact of premarital sexual behaviour among adolescents.